Vascular Architecture Alterations Independent of Lipid Profiles: The Paradoxical Dissociation between Dyslipidemia and Carotid Intima-Media Thickness in Obese Adolescents - Yenny Astari; Didik Hariyanto; Eka Agustia Rini; Eva Chundrayetti; Nice Rachmawati Masnadi; Anggia Perdana Harmen; Rinang Mariko (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Adolescent obesity is a global epidemic that initiates subclinical atherosclerosis. While lipid profiles are traditional markers, their correlation with structural vascular changes in the pediatric population remains a subject of intense academic debate. This study evaluates the relationship between traditional lipid parameters and carotid intima-media thickness (CIMT) in obese high school students. Methods: An observational cross-sectional study was conducted between January 2025 and January 2026 involving 45 obese adolescents aged 15 to 18 years in Padang, Indonesia. Nutritional status was determined using the CDC 2000 growth charts, specifically targeting those with a body mass index at or above the 95th percentile. CIMT was measured via high-resolution B-mode ultrasonography. Lipid profiles, including total cholesterol, triglycerides, HDL, and LDL, were analyzed through laboratory testing. Statistical analysis utilized Fisher’s exact test through SPSS version 22. Results: The subjects, of whom 68.9 percent were female, had a median BMI of 29.34 ± 2.03 kg/m². Remarkably, 68.9 percent exhibited CIMT thickening above the 75th percentile. Bivariate analysis revealed no significant association between CIMT and total cholesterol (p=0.402), triglycerides (p=0.696), HDL (p=0.563), or LDL (p=1.000). Conclusion: Vascular remodeling in obese adolescents occurs independently of circulating lipid levels, suggesting that chronic inflammation may drive early atherosclerosis before clinical dislipidemia manifests.